Pharmacokinetics and bioavailability of tocotrienols in healthy human volunteers: a systematic review - Sharif, Mahjabeen; Khan, Dilshad Ahmed; Farhat, Kulsoom; Mudassar Noor,; Mohammad Asghar Khan,; Saima Rafique, (Journal of the Pakistan Medical Association, 2023)
Objectives: To evaluate and compare the pharmacokinetic parameters, especially bioavailability, of annatto-based tocotrienol with palm tocotrienol-rich fraction in healthy human volunteers for better therapeutic outcome. Method: The systematic review was conducted between April and August 2021 in accordance with the Preferred Reporting Items for Systematic Review and Meta Analysis guidelines, and comprised search on PubMed, Google Scholar, Pakmedinet and Google search engines for open-label or double-blind randomised controlled trials involving healthy human volunteers published till January 2021. Key words used included annatto-based tocotrienol, palm tocotrienol-rich fraction, absorption and bioavailability. Boolean operators were also used, like tocotrienol AND bioavailability, annatto tocotrienol AND pharmacokinetics. Results: Of the 230 articles identified, 50(21.7%) articles met the eligibility criteria. Of them, 7(14%) were selected for data extraction and detailed analysis. Pharmacokinetic parameters of annatto-based tocotrienol were better than palm-derived tocotrienol. Oral administration of all the isomers of annatto-based tocotrienols resulted in dose-dependent increase in area under curve and plasma levels. Amongst all the isomers of annatto-based and palm-derived tocotrienol, delta isomer of annatto-based tocotrienol had the highest bioavailability with area under curve 7450±89 ng/ml, time to reach peak plasma levels 4 hours, maximum plasma concentration 1591±43 ng/nl and elimination half-life 2. 68 ±0.29 hrs. Pharmacokinetic parameters of delta isomer of annatto-based tocotrienol was greater than palm tocotrienol-rich fraction. Conclusion: Bioavailability of annatto-based tocotrienol was better than that of palm-derived tocotrienol-rich fraction. Delta isomer of annatto-based tocotrienol had the highest bioavailability amongst all isomers of tocotrienol.